Continuous ambulatory peritoneal dialysis technique failure in adult patients treated at a tertiary hospital in central South Africa: a retrospective analytical study - Tshifhiwa B. Sikhipha; Claire Barrett; Nicoline van Zyl; Cornel van Rooyen; Feziwe B. Bisiwe (BMC Nephrology)
Abstract Background Continuous ambulatory peritoneal dialysis (CAPD) is one of the kidney replacement therapy (KRT) modalities used in patients with kidney failure. It is the preferred modality in most resource-limited settings as it is more accessible and cost-effective. CAPD technique failure remains a challenge and is associated with an increased risk of morbidity and mortality. We aimed to describe the sociodemographic and clinical characteristics, CAPD survival rate and the reasons for CAPD technique failure over a five-year period among adult patients on CAPD at a tertiary hospital in South Africa. Methods We conducted a retrospective analytical study reviewing files of patients with end-stage kidney disease (ESKD) whose peritoneal dialysis (PD) catheter was removed, or who died with a functioning PD catheter while on the PD program at Universitas Academic Hospital in Bloemfontein, South Africa, from 01 January 2015 until 31 December 2019. The demographic, clinical and laboratory data were collected from patients' medical records. Clinical outcomes were technique failure and survival. Results Ninety-one patient records met the inclusion criteria of whom 51 (56.0%) were male. The median age at commencement of PD was 40 years (interquartile range [IQR] 18–58). Fifty-one (57.3%) patients were single and 64 (70.0%) were unemployed. Hypertension was the leading cause of ESKD (n = 47; 51.6%), followed by human immunodeficiency virus- (HIV-) associated conditions (n = 18; 19.8%). Technique failure rates at 1-, 2-, 3-, 4- and 5-years post-PD initiation were 31.9%, 35.2%, 13.2%, 8.8% and 11.0%, respectively. The 5-year survival rate was 63.7% (n = 58), with a median survival time of 26 months (IQR 1–54). Peritonitis was the leading cause of technique failure (n = 52; 57.1%), and almost a third (n = 29 (31.9%)) had a fatal outcome. Younger age and using the Dianeal® PD system were associated with an increased likelihood of technique failure. No other sociodemographic, laboratory and clinical factors were associated with the development of technique failure or death. Conclusions PD-associated peritonitis is the primary cause of technique failure, followed by sudden unexpected death occurring at home. Preventive measures need to be adhered to in order to avoid high rates of peritonitis.